(untitled) (SCIENCE TIME JOURNAL, 2026)
This research analyzes the main theoretical and methodological approaches developed so far to enhance students’ speech competence in the process of language learning. The study examines communicative, cognitive, competency-based, interactive, and learner-centered approaches, highlighting their principles, advantages, and practical applications in developing speaking skills. Special attention is given to strategies that foster fluency, accuracy, critical thinking, and spontaneous speech production. The research also discusses modern pedagogical technologies and their role in improving oral communication in educational settings. The findings demonstrate that an integrated approach combining traditional and innovative methods contributes significantly to the effective development of students’ speech abilities.